Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Kebijakan Dividen terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Aufanul Ichsan (Pascasarjana Universitas Sultan Ageng Tirtayas, 2022)
This study aims to examine the effect of Investment Decision, Funding Decision, and DividendPolicy on Firm Value with Firm Size as Moderating Variable in Manufacturing Firm’s listed on theIndonesia Stock Exchange during the 2018-2021 period. The technique used for sampling in this studyis the purposive sampling method. In addition, the regression analysis model used in this study isModerated Regression Analysis (MRA). The results of this study found that the Investment Decision(PER) has a negative and significant effect on Firm Value (PBV), Funding Decision (DER) has anegative and significant effect on Firm Value, and Dividend Policy (DPR) has no effect on Firm Value.In addition, the results of this study prove that firm size (SIZE) is able to moderate (weaken) the effect of Investment Decisions on Firm Value, Firm Size is able to moderate (weaken) the effect of Investment Decisions on Firm Value, and Firm Size cannot moderate the effect of dividend policy on Firm Value.